(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Purwanto H, Soesilohadi RCH, Trianto M. 2022. Stingless bees from meliponiculture in South Kalimantan, Indonesia. Biodiversitas 23: 1254-1266. Kalimantan Island has many species of stingless bees that are widespread throughout the province. However, their morphology, morphometry, and nest structure characteristics have not been documented comprehensively. This paper described the morphological characters, morphometric measurements, nest entrance, and brood cell characteristics of stingless bees from meliponiculture in South Kalimantan, Indonesia. Ten stingless bee species were identified based on their morphological features: Tetragonula laeviceps (Smith, 1857), T. fuscobalteata (Cameron, 1908), T. drescheri (Schwarz, 1939), T. melanocephala (Gribodo, 1893), T. biroi (Friese, 1898), Homotrigona apicalis (Smith, 1857), H. canifrons (Smith, 1857), Heterotrigona itama (Cockerell, 1918), Geniotrigona thoracica (Smith, 1857), and Lepidotrigona terminata (Smith, 1878). Principal component analysis was performed to identify the grouping characters and thus determine their diagnostic characters. Furthermore, the shape, diameter, length, ornamentation, and color of the nest entrance and the arrangement, cells, and color of brood cells were observed. This study is the first to report high variations in the type of entrance opening and arrangement of brood cells for stingless bee species, which are abundant in South Kalimantan.